2021
DOI: 10.3390/md19040223
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Larvicidal Activities of Phlorotannins from Brown Seaweeds

Abstract: Phlorotannins are secondary metabolites produced by brown seaweeds with antiviral, antibacterial, antifungal, and larvicidal activities. Phlorotannins’ structures are formed by dibenzodioxin, ether and phenyl, ether, or phenyl linkages. The polymerization of phlorotannins is used to classify and characterize. The structural diversity of phlorotannins grows as polymerization increases. They have been characterized extensively with respect to chemical properties and functionality. However, review papers of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…The level of larvicidal and inhibitory effect of crude phlorotannin extracted from E. cava appears to be relatively lower than crude phlorotannin from some other brown seaweed species. Many studies have reported that marine macroalgae in the Phaeophyta group contain a number of biodynamic compounds with their respective cytotoxic properties [ 16 , 17 , 19 , 57 ]. Phlorotannin, as a bio-compound of brown seaweed, may also have a different bioactivity and toxicity, depending on several factors, including structural composition and molecular weight [ 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of larvicidal and inhibitory effect of crude phlorotannin extracted from E. cava appears to be relatively lower than crude phlorotannin from some other brown seaweed species. Many studies have reported that marine macroalgae in the Phaeophyta group contain a number of biodynamic compounds with their respective cytotoxic properties [ 16 , 17 , 19 , 57 ]. Phlorotannin, as a bio-compound of brown seaweed, may also have a different bioactivity and toxicity, depending on several factors, including structural composition and molecular weight [ 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phlorotannins are also toxic to other organisms. Recent scientific reviews of the toxicity and larvicidal activity of phlorotannins in organisms have been compiled [ 16 , 17 ]. Larvicidal studies of phlorotannins in mosquito larvae have also been widely reported [ 18 , 19 , 20 ], as well as in some marine invertebrates, such as ascidians Ciona savignyi and Halocynthia roretzi [ 21 ]; tube-building polychaete, Hydroides elegans [ 22 ]; mussel, Mytilus edulis [ 23 ]; blue crab, Portunus trituberculatus [ 24 ]; barnacle, Balanus improvisus [ 9 ]; coral, Acropora millepora [ 25 ]; and brine shrimp, Artemia salina [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are more concentrated in the epidermal cortex of algae, although they have also been found in the cell wall of marine macroalgae (Petchidurai et al, 2019). Various studies have shown that phlorotannins have various biological activities including antioxidant (Kang et al, 2011;Sathya et al, 2017;Wang et al, 2012), antibacterial (Vázquez-Rodríguez et al, 2021), antifungal (Negara et al, 2021), antiviral (Ahn et al, 2004;Kwon et al, 2013), antiparasitic (Haavisto et al, 2017), anti-cancer (Imbs & Zvyagintseva, 2018), anti-diabetic (Erpel et al, 2020;Lee & Jeon, 2013), antihypertensive (McFarlane et al, 2003), anti-proliferative (Nwosu et al, 2011), anti-inflammatory (Lopes et al, 2012), and anti-allergic activities (Shim et al, 2009).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…These compounds are more concentrated in the epidermal cortex of algae, although they have also been found in the cell wall of marine macroalgae (Petchidurai et al., 2019). Various studies have shown that phlorotannins have various biological activities including antioxidant (Kang et al., 2011; Sathya et al., 2017; Wang et al., 2012), antibacterial (Vázquez‐Rodríguez et al., 2021), antifungal (Negara et al., 2021), antiviral (Ahn et al., 2004; Kwon et al., 2013), antiparasitic (Haavisto et al., 2017), anti‐cancer (Imbs & Zvyagintseva, 2018), anti‐diabetic (Erpel et al., 2020; Lee & Jeon, 2013), antihypertensive (McFarlane et al., 2003), anti‐proliferative (Nwosu et al., 2011), anti‐inflammatory (Lopes et al., 2012), and anti‐allergic activities (Shim et al., 2009). They also have enzymatic inhibitory effects such as inhibition of α‐glucosidase and α‐amylase (Lee et al., 2009), inhibition of acetylcholinesterase (AChE) and butylcholinesterase (BChE) (Massoulié et al., 1993), inhibition of angiotensin‐1 converting enzyme (ACE‐I) (Jung et al., 2006), inhibition of metalloproteinases (MMPs) (Kim et al., 2006), inhibition of hyaluronidases (Shibata et al., 2002), and inhibition of tyrosinase (Kang et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, brown macroalgae have been used to treat goiter and obesity [7]. In East Asia, brown macroalgae from the genera Laminaria, Undaria, and Sargassum (formerly Hizikia) are widely consumed daily and used as herb medicine [8][9][10][11][12]. Hence, the bioactive properties of brown macroalgae have drawn the attention of researchers.…”
Section: Introductionmentioning
confidence: 99%